Dinâmica do nitrogênio sob sistema plantio direto e parâmetros para o manejo da adubação nitrogenada no milho - Acosta, José Alan de Almeida (2009)
Among the several essential nutrients in the nutrition of the maize, without a doubt, the nitrogen (N) is one of the most important. However, most of the time, the amount naturally available in the soil is insufficient to supply the demand for N, turning the complementation with nitrogen fertilization to maize essential for obtaining of expressive yields, besides to represent a significant part of the production costs. In that way, the rational use of nitrogen fertilization associated to the best use of the N released by residues cultural predecessors is an aspect of extreme importance for the maize production inside of scenery economically viable and correct ecologically. The main objective of this work was to study the N availability dynamics in the soil influenced by residues from cover crops predecessors and to evaluate the use of new technologies to nitrogen fertilizer management in the maize in no-tillage system (NT). For that, specifics and supplementary studies were carried out, looking to evaluate the residues decomposition dynamics and N release (Chapter I); the soil N availability effects (Chapter II); the N absorption until flower stage and maize yield in function of the amount of residues added by different combination of cover crops and N fertilizer levels in NT (Chapter III). Also the N fertilizer value was evaluated from hairy vetch residues to maize using 15N-isotope techniques (Chapter IV) and the comparative use of soil and plants parameters to N fertilizer variable rate recommendation in the maize, looking to increase the efficiency of the N applied (Chapter V). The rates of decomposition were not significantly influenced by amounts of residues added in the soil, but the N mineralization and immobilization processes were intensified. Already the addition and residues decomposition dynamics influenced directly the mineral N availability in the soil when not compared to the addition of residues. The influence in the N availability dynamics in function of the addition of residues was evident in the results of N accumulation until flower stage and in the transformation of this N accumulated in yield grains. The results showed that maize yield was directly proportional to N absorption and that maize sowed in succession hairy vetch presented larger production capacity in relation to black oat and oil radish residues, even with N fertilizer supplementary. The yields upper to 9 Mg grains ha-1 only was possible with accumulated upper to 150 kg N ha-1 until flower stage, and only in the succession hairy vetch/maize was possible to reach such amount. However, in spite of the recognized capacity to N supply of the hairy vetch residues, associated the biologic nitrogen fixation capacity this cover crop and higher N addition to soil, the N maximum recovery was 27% the first year and 5% in the second year. Like this, it is concluded that the maize N recovery after hairy vetch is lower to be totally responsible for the yield increase, suggesting that the hairy vetch may have a positive effect besides of the N supply. The group of results suggests that the higher N availability in the initial phase of the maize development provided by fast hairy vetch decomposition is an essential factor in the increase of the yield usually observed in the succession hairy vetch/maize. Verified still the parameters of plants presented the best performance in the diagnosis of the demand of N for the maize in relation to the soil parameters, improving the synchronization between availability and demand, spatially variable during the maize development.